Perencanaan sumber daya manusia sebagai strategi peningkatan efektivitas dan daya saing organisasi - Maharani, Aulia Sekar (Maliki Interdisciplinary Journal, 2026)
Human resource planning (HRP) is a strategic process that plays an essential role in ensuring organizational sustainability and success. This article discusses the concepts, objectives, stages, influencing factors, and challenges of human resource planning. HRP aims to ensure the availability of the right workforce in terms of quantity, quality, and competence according to organizational needs at the right time. The stages of HRP include job analysis, preparation of job descriptions and job specifications, implementation of work analysis, and regular maintenance and updating of job data. In addition, HRP is influenced by internal and external factors, such as government policies, workforce quality, technological changes, labor market conditions, and corporate business strategies. In its implementation, organizations often face several challenges, including limited data, uncertainty in the business environment, lack of management support, and resistance from employees and employers. Therefore, adaptive strategies, adequate human resource information systems, and strong coordination between management and employees are required. Effective HRP enables organizations to improve operational efficiency, strengthen competitiveness, and achieve both short-term and long-term goals sustainably.